2001
DOI: 10.1055/s-2001-16936
|View full text |Cite
|
Sign up to set email alerts
|

Hormones and Hormone Antagonists: Mechanisms of Action in Carcinogenesis of Endometrial and Breast Cancer

Abstract: Proliferation of breast and endometrial cells is under the control of ovarian steroid hormones (SHs) such as oestrogen and progesterone. They mediate diverse physiological functions via interaction with nuclear-localised steroid hormone receptors (HRs). The SH receptor complex modifies the expression of SH-regulated genes by binding to conserved binding sites in their promoter region or through cross-talk with other transcription factors. In non-malignant tissues, HRs are in balance with other factors regulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
39
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(39 citation statements)
references
References 53 publications
0
39
0
Order By: Relevance
“…In support of our findings, previous studies (27-29) have shown beneficial effects of HRT use for lung cancer risk. For example, Kreuzer et al The potential of estrogens to initiate and promote tumor growth in female reproductive organs by interacting with estrogen receptors, which are also present in both normal (40) and malignant lung tissue (40 -42), is well established (41,43,44). However, their role in lung cancer tumorigenesis is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…In support of our findings, previous studies (27-29) have shown beneficial effects of HRT use for lung cancer risk. For example, Kreuzer et al The potential of estrogens to initiate and promote tumor growth in female reproductive organs by interacting with estrogen receptors, which are also present in both normal (40) and malignant lung tissue (40 -42), is well established (41,43,44). However, their role in lung cancer tumorigenesis is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…The collective evidence supports contributions to estrogensensitive breast cancer from both the proliferative and antiapoptotic hormonal effects of estrogen itself (12)(13)(14)(15)(16) and the genotoxic and mutagenic effects of estrogen metabolites (17,18). In human breast tissue, estrogen metabolites have been detected (19), and DNA adducts of equine estrogens have been reported (20).…”
mentioning
confidence: 94%
“…Regulation of proliferation and differentiation and essential pathways involved in the physiological action of estrogen and progesterone in target tissues are well documented (Graham and Clarke, 1997;Sutherland et al, 1998). Furthermore, several in vivo and in vitro reports clearly indicate that these hormones are also implicated in the control of cell loss by apoptosis (Kumar et al, 2000), but these data remain controversial because, depending on the experimental model, both anti-and pro-apoptotic activity has been ascribed to each hormone (Flototto et al, 2001).…”
Section: Introductionmentioning
confidence: 99%